Clinical characteristics of two‐hundred thirty‐two dogs (2006–2018) treated for suspected anaphylaxis in Perth, Western Australia. Issue 12 (19th September 2021) - Turner, K; Boyd, C; Stander, N; Smart, L
Abstract : Objective: To describe the clinical features of dogs treated for suspected anaphylaxis in Perth, Western Australia. Design: Single‐centre observational case series with retrospective and prospective phases. Methods: This was a two‐phase study of dogs with clinical suspicion of anaphylaxis presenting to the emergency service of a university teaching hospital. Dogs required evidence of, and appropriate treatment of, a type 1 hypersensitivity reaction as well as two or more organs affected (or cardiovascular signs alone) to be included. Phase 1 includes retrospective case series of 186 dogs (March 2006–December 2018). Phase 2 includes prospective descriptive case series of 46 dogs (October 2017–July 2018) focused on clinical signs. Results: In phase 1, 88 (47%) dogs had evidence of insect exposure prior to the acute event. One hundred forty (75%) dogs had dermatological signs, 141 (76%) had gastrointestinal signs and 129 (69%) had cardiovascular signs. Ninety‐two (49%) dogs had vasoconstrictive shock (5 with bradycardia), 24 (13%) had vasodilatory shock, 8 (4%) had mixed vasodilatory and vasoconstrictive shock and 5 (3%) had unclassifiable shock. On focused abdominal ultrasound, 42 of 71 (59%) dogs had gallbladder wall oedema and 3 of 71 (4%) dogs had peritoneal free fluid. In phase 2, the distributions of insect exposure, organ dysfunction and sonographic abnormalities were similar to phase 1. Conclusion: Dogs presenting with suspected anaphylaxis showed a broad range of presentations. Dermatological signs were absent in a proportion of dogs, vasoconstrictive shock was more frequent than vasodilatory and unique features of shock were identified. This study highlights the challenges of diagnosis based on presenting features alone.